Nodal Anaplastic Large-Cell Lymphoma ALK-1− with CD30+ Cutaneous Lymphoproliferation Treated with Mistletoe: Spontaneous Remission or Treatment Response? - Kameda, G.; Kempf, W.; Oschlies, I.; Michael, K.; Seifert, G.; Längler, A. (Klinische Pädiatrie, 2011)
A 12-year old girl presented with general weakness and weight loss, a localised cervical lymph node enlargement and cutaneous lesions compatible with lymphomatoid papulosis (LyP). Biopsies from lymph node and skin revealed a histological diagnosis of nodal large cell ALK-1− anaplastic lymphoma (ALCL) with a synchronous CD30+ cutaneous lymphoproliferation consistent with lymphomatoid papulosis (LyP). The girl was treated with mistletoe (MT) as monotherapy. Within 1 week after initiation of MT-treatment the skin lesions and lymph node enlargement improved. Under continuing MT-therapy 30 months after diagnosis the patient is still in complete remission. It is not possible to know whether this was a rare case of spontaneous remission of the nodal and skin-manifestations of this CD30+ T-cell lymphoproliferation or whether the observed effect was a specific therapeutic response to MT-treatment.
Keywords: lymphomatoid papulosis; primary cutaneous CD30+ T-cell lymphoproliferation; mistletoe; complementary and alternativ medicine